Buying behaviour of farmers - Kool, Maarten (1994)
This work examines the buying behaviour of farmers. Purchasing has become an important management task on the farm. Farmers spend at least 60 per cent of their farm revenues on inputs purcahsed from off-farm suppliers. The farm supply industry is confronted with an increasing level of competition as a result of three important trends: (1) stablizing of shrinking markets; (2) internalization; (3) shorter product life cycles. These aspects have increased the need for understanding farmers' buying behaviour. The text provides firstly a general model of farmers' buying behaviour which is developed to identify key variables in this behaviour, and provides a framework for their relationships and their function. Secondly, a number of hypotheses on farmers' buying behaviour are empirically tested.